Brønsted Acid‐Promoted Cascade Alkylation/Cyclization of Pyrroles with N, N‐Dimethylaminomethyleneglutaconic Acid Dinitrile: A Concise Route to Cyclopenta[b]pyrroles. Issue 14 (11th September 2015) - Wu, Kaikai; Wu, Ping; Chen, Jiping; Sun, Chenglin; Yu, Zhengkun
Abstract: A Brønsted acid ( p ‐TsOH⋅H2 O) promoted alkylation/cyclization cascade reaction of pyrroles with N, N ‐dimethylaminomethyleneglutaconic acid dinitrile was efficiently realized to afford functionalized cyclopenta[ b ]pyrroles with excellent diastereoselectivity. Deamination of the corresponding ammonium salts of the cyclopenta[ b ]pyrroles with methyl iodide led to dihydrocyclopenta[ c ]pyrroles. The cascade reaction pathway was confirmed by isolation and transformation of the reaction intermediate, i.e., the 2‐alkylated pyrrole. Abstract :